Fluorescent carbon dot with room-temperature phosphorescence performance as well as preparation method and application of fluorescent carbon dot

The carbon dots prepared by hydrothermal reaction, combined with polyethyleneimine and thiamine hydrochloride, solve the problems of low fluorescence intensity and short phosphorescence time of existing carbonated polymer dots, achieve efficient fluorescence and phosphorescence performance, and expand its application in various fields.

CN119842396AActive Publication Date: 2025-04-18QUANZHOU NORMAL UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510057072.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-18
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The carbonized polymer dots prepared in the prior art generally have only fluorescence characteristics and have a low fluorescence intensity, or although they have a phosphorescence effect, the phosphorescence time is short, which limits their application.

Method used

By mixing polyethyleneimine, thiamine hydrochloride and water, and carrying out hydrothermal reaction, fluorescent carbon dots with room temperature phosphorescence properties were prepared.

Benefits of technology

The prepared carbon dots have both fluorescence and phosphorescence characteristics, high fluorescence intensity and long phosphorescence time, and are suitable for the preparation of luminescent materials, biomedicine, optoelectronic devices and sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842396A_ABST
    Figure CN119842396A_ABST
Patent Text Reader

Abstract

The invention provides a fluorescent carbon dot with room-temperature phosphorescence performance as well as a preparation method and application thereof, and belongs to the technical field of carbon dots. The preparation method provided by the invention comprises the following steps: (1) mixing polyethyleneimine, thiamine hydrochloride and water to obtain a mixed solution; and (2) carrying out hydrothermal reaction on the mixed solution obtained in the step (1) to obtain the fluorescent carbon dots with room-temperature phosphorescence performance. Polyethyleneimine and thiamine hydrochloride are adopted as raw materials, and the prepared carbon dots have fluorescence and phosphorescence characteristics and are high in fluorescence intensity and long in phosphorescence afterglow time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of carbon dots, and in particular relates to fluorescent carbon dots with room temperature phosphorescence performance, and a preparation method and application thereof. Background Art

[0002] Fluorescent carbon dots are a type of carbon nanomaterial with excellent optical properties, and they play an important role in the fields of biomedicine, optoelectronic devices, sensors, etc. According to the differences in the carbon core and its surface state, carbon dots can be divided into graphene quantum dots, carbon nanodots, and carbonized polymer dots. Carbonized polymer dots not only integrate the excellent chemical stability and high luminescence performance of traditional carbon dots, but also the outer layer structure of the polymer chain formed can avoid the self-quenching effect caused by aggregation of the luminescence center. The carbonized polymer dots prepared in the prior art generally only have fluorescent properties and low fluorescence intensity, or have phosphorescence effects but short phosphorescence time, which limits their application. Therefore, how to obtain a carbon dot that has both fluorescent and phosphorescence properties and has high fluorescence intensity and long phosphorescence time has become a difficult problem in the prior art. Summary of the invention

[0003] The purpose of the present invention is to provide a fluorescent carbon dot with room temperature phosphorescence performance and a preparation method and application thereof. The carbon dot prepared by the present invention has both fluorescence and phosphorescence properties, and has high fluorescence intensity and long phosphorescence time.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing fluorescent carbon dots with room temperature phosphorescence performance, comprising the following steps:

[0006] (1) mixing polyethyleneimine, thiamine hydrochloride and water to obtain a mixed solution;

[0007] (2) subjecting the mixed solution obtained in step (1) to a hydrothermal reaction to obtain fluorescent carbon dots having room temperature phosphorescence properties.

[0008] Preferably, the weight average molecular weight of the polyethyleneimine in step (1) is 600 to 70,000.

[0009] Preferably, in step (1), the mass ratio of polyethyleneimine to thiamine hydrochloride is 0.5:(0.02-1.6).

[0010] Preferably, the pH value of the mixed solution in step (1) is 5-10.

[0011] Preferably, in step (1), the mass ratio of polyethyleneimine to water is 1:(20-40).

[0012] Preferably, the temperature of the hydrothermal reaction in step (2) is 120 to 200° C., and the time of the hydrothermal reaction is 2 to 16 hours.

[0013] Preferably, the temperature of the hydrothermal reaction is 180° C., and the time of the hydrothermal reaction is 14 h.

[0014] The present invention also provides fluorescent carbon dots with room temperature phosphorescence properties prepared by the preparation method described in the above technical solution.

[0015] The present invention also provides the use of the fluorescent carbon dots with room temperature phosphorescence properties described in the above technical solution in the preparation of luminescent materials, biomedicine, optoelectronic devices and sensors.

[0016] Preferably, the luminescent material comprises a carbon dot-boron oxide composite material or a carbon dot-polymer composite film.

[0017] The present invention provides a method for preparing fluorescent carbon dots with room temperature phosphorescence performance, comprising the following steps: (1) mixing polyethyleneimine, thiamine hydrochloride and water to obtain a mixed solution; (2) subjecting the mixed solution obtained in the step (1) to a hydrothermal reaction to obtain fluorescent carbon dots with room temperature phosphorescence performance. The present invention uses polyethyleneimine and thiamine hydrochloride as raw materials, and the prepared carbon dots have both fluorescence and phosphorescence characteristics, and at the same time have high fluorescence intensity and long phosphorescence afterglow time. The results of the embodiment show that the carbon dot solution prepared by the present invention emits blue fluorescence with a wavelength of 458nm under the excitation of a 335nm light source, and the prepared carbon dot boron oxide composite material solid powder shows blue fluorescence under a 365nm lamp, and has green phosphorescence emission at 525nm, with high fluorescence intensity. After being irradiated with a 365nm ultraviolet lamp for 2s and then turned off, it can continuously emit nearly 7s of room temperature phosphorescence. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The fluorescence spectra of the carbon dot solutions prepared in Examples 1 to 4;

[0019] Figure 2 The fluorescence spectra of the carbon dot solutions prepared in Examples 1 and 5 to 9;

[0020] Figure 3 The fluorescence spectra of the carbon dot solutions prepared in Examples 1 and 18 to 22;

[0021] Figure 4 The fluorescence spectra of the carbon dot solutions prepared in Examples 1 and 23 to 30;

[0022] Figure 5 The fluorescence spectra of the carbon dot solutions prepared in Examples 1 and 31 to 34;

[0023] Figure 6The fluorescence spectra of the carbon dot solutions prepared in Example 1 and Comparative Examples 1 to 4;

[0024] Figure 7 This is the fluorescence spectrum of the carbon dot solution prepared in Example 1 after being diluted 10 times;

[0025] Figure 8 This is the ultraviolet absorption spectrum of the carbon dot solution prepared in Example 1 after being diluted 100 times;

[0026] Fig. 9 This is a transmission scanning electron microscopy image of the carbon dot solution prepared in Example 1;

[0027] Fig.10 This is a particle size distribution diagram of the carbon dot solution prepared in Example 1;

[0028] Fig.11 The fluorescence spectra of the carbon dot solution prepared in Example 1 at different excitation wavelengths after being diluted 10 times;

[0029] Fig.12 It is a curve diagram of different excitation wavelengths and fluorescence intensities after the carbon dot solution prepared in Example 1 was diluted 10 times;

[0030] Fig.13 The fluorescence spectra of the carbon dot solution prepared in Example 1 after being diluted 10 times under light irradiation at different times;

[0031] Fig.14 The fluorescence spectra of the carbon dot solution prepared in Example 1 in buffer solutions with different pH values;

[0032] Fig.15 The phosphorescence spectra of the carbon dot boron oxide composite material prepared in Application Example 1 at different temperatures;

[0033] Fig.16 The phosphorescence lifetime curves of the carbon dot boron oxide composite material prepared in Application Example 1 at different temperatures;

[0034] Fig.17 The phosphorescence spectrum of the carbon dot boron oxide composite material prepared in Application Example 1 is a temperature reversibility graph;

[0035] Fig.18 The macroscopic images of the carbon dot boron oxide composite material prepared in Application Example 1 after irradiation with visible light, 254nm and 365nm ultraviolet lamps for 2s, and at different times after turning off the ultraviolet lamp;

[0036] Fig.19 The macroscopic images of the carbon-dot boron oxide composite material prepared in Application Example 1 and the materials prepared in Comparative Application Examples 1 to 7 after irradiation with a 365nm ultraviolet lamp for 2s and at different times after the ultraviolet lamp is turned off;

[0037] Fig. 20 The tensile stress-strain curves of the films prepared in Application Example 2 and Comparative Application Example 8;

[0038] Fig.21 These are macroscopic images of the films prepared in Application Example 2 and Comparative Application Example 8 under UV light and sunlight after stretching. DETAILED DESCRIPTION

[0039] The present invention provides a method for preparing fluorescent carbon dots with room temperature phosphorescence performance, comprising the following steps:

[0040] (1) mixing polyethyleneimine, thiamine hydrochloride and water to obtain a mixed solution;

[0041] (2) subjecting the mixed solution obtained in step (1) to a hydrothermal reaction to obtain fluorescent carbon dots having room temperature phosphorescence properties.

[0042] Unless otherwise specified, the present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.

[0043] The invention mixes polyethyleneimine, thiamine hydrochloride and water to obtain a mixed solution.

[0044] In the present invention, the weight average molecular weight of the polyethyleneimine is preferably 600 to 70,000, more preferably 1,800 to 10,000, and further preferably 1,800. By controlling the weight average molecular weight of polyethyleneimine within the above range, the luminescence intensity of the carbon dots can be further improved.

[0045] In the present invention, the mass ratio of polyethyleneimine to thiamine hydrochloride is preferably 0.5:(0.02-1.6), more preferably 0.5:(0.04-0.8), further preferably 0.5:(0.08-0.5), and most preferably 0.5:0.08. The present invention controls the mass ratio of polyethyleneimine to thiamine hydrochloride within the above range, which can further improve the luminescence intensity of carbon dots.

[0046] In the present invention, the mass ratio of polyethyleneimine to water is preferably 1:(20-40), more preferably 1:30. In the present invention, the mass ratio of polyethyleneimine to water is controlled within the above range, so that the raw materials can be fully dissolved.

[0047] In the present invention, the pH value of the mixed solution is preferably 5 to 10, more preferably 6 to 9, and further preferably 7 to 8. In the present invention, the pH value of the mixed solution is controlled within the above range, which can further improve the luminescence intensity of the carbon dots.

[0048] In the present invention, when the pH value of the mixed solution is not within the above range, the present invention preferably adds an acid or a base to adjust the pH value of the mixed solution. In the present invention, the acid is preferably hydrochloric acid; the base is preferably a sodium hydroxide solution. The present invention has no particular limitation on the concentration and amount of the acid or base, as long as the pH value of the mixed solution is within the above range.

[0049] In the present invention, the mixing of polyethyleneimine, thiamine hydrochloride and water is preferably carried out under ultrasonic conditions. The present invention has no particular limitation on the power and time of the ultrasound, and the technical solutions well known to those skilled in the art can be used to ensure that the raw materials are fully dissolved and mixed uniformly.

[0050] After obtaining the mixed solution, the present invention performs a hydrothermal reaction on the mixed solution to obtain fluorescent carbon dots with room temperature phosphorescence performance.

[0051] In the present invention, the temperature of the hydrothermal reaction is preferably 120-200°C, more preferably 140-180°C, and further preferably 160-180°C; the time of the hydrothermal reaction is preferably 2-16h, more preferably 4-14h, and further preferably 10-14h. The present invention controls the temperature and time of the hydrothermal reaction within the above range, which can further improve the luminescence intensity of the carbon dots.

[0052] After the hydrothermal reaction is completed, the present invention preferably filters, dialyzes, concentrates and dries the product of the hydrothermal reaction in sequence to obtain fluorescent carbon dots with room temperature phosphorescence properties.

[0053] In the present invention, the filtration preferably uses a syringe filter of an aqueous membrane; the pore size of the syringe filter of the aqueous membrane is preferably 0.4-0.5 μm, more preferably 0.45 μm. The present invention has no particular limitation on the model of the syringe filter of the aqueous membrane, and any model well known to those skilled in the art can be used.

[0054] In the present invention, the molecular weight cut-off during dialysis is preferably 450 to 550 Da, more preferably 500 Da.

[0055] In the present invention, the dialysis time is preferably 40 to 50 hours, more preferably 48 hours.

[0056] In the present invention, the concentration temperature is preferably 70-90°C, more preferably 80°C; the concentration is preferably performed under vacuum conditions. The present invention has no particular limitation on the vacuum degree of the vacuum conditions and the concentration time, and the technical solutions well known to those skilled in the art can be used.

[0057] The present invention has no particular limitation on the drying temperature and time, and the technical solutions well known to those skilled in the art may be adopted.

[0058] The invention adopts polyethyleneimine and thiamine hydrochloride as raw materials, and the prepared carbon dots have both fluorescence and phosphorescence properties, and at the same time, the fluorescence intensity is high and the phosphorescence afterglow time is long.

[0059] The present invention also provides fluorescent carbon dots with room temperature phosphorescence properties prepared by the preparation method described in the above technical solution.

[0060] The carbon dots prepared by the present invention are yellow solids, present a highly dispersed spherical state, are relatively uniform in size, have an average particle size of about 4.28nm, are soluble in water and present a uniform transparent yellow solution, the carbon dot aqueous solution presents a positively charged surface state under different pH conditions, the zeta potential value is +19.07mV under the pH=2.87 aqueous solution condition, and displays blue fluorescence under a 365nm lamp, the optimal excitation wavelength is 335nm, the emission wavelength is 458nm, and there is green phosphorescence emission at 525nm, the phosphorescence intensity decreases with increasing temperature, and has a temperature reversibility of 20-80°C; the luminescence performance is stable, has good excitation wavelength independence and spectral stability, the fluorescence quantum yield is 18.87%, and the carbon dot aqueous solution has film-forming properties.

[0061] The present invention also provides the use of the fluorescent carbon dots with room temperature phosphorescence properties described in the above technical solution in the preparation of luminescent materials, biomedicine, optoelectronic devices and sensors.

[0062] In the present invention, the luminescent material preferably includes a carbon dot-boron oxide composite material or a carbon dot-polymer composite film.

[0063] The present invention has no special limitation on the preparation method of the carbon dot-boron oxide composite material or the carbon dot-polymer composite film, and the technical schemes well known to those skilled in the art can be adopted.

[0064] In an embodiment of the present invention, the preparation method of the carbon dot boron oxide composite material is: dissolve 2.0g of boric acid in 40mL of ultrapure water and then add 2mL of 60mg / mL carbon dot aqueous solution, ultrasonically mix for 10min, cover the mouth of the beaker with aluminum foil, put it in an oven at 180°C and heat it for 5h, and naturally cool it to room temperature to obtain an amorphous glassy carbon dot boron oxide composite material.

[0065] In an embodiment of the present invention, the preparation method of the carbon dot polymer composite film is as follows: weigh 1g of PVA into a dry beaker, add 1mL of a carbon dot aqueous solution with a concentration of 60mg / mL, dilute to 10mL with ultrapure water, stir in a 90°C water bath for 30min until the PVA is completely dissolved, mix evenly until the bubbles disappear, pour onto a film-forming glass plate, and use an adjustable film-forming device to prepare a film with a film thickness of 0.05mm. Place the film-forming glass plate in an oven and dry it at 35°C for 2h, then cool it to form a carbon dot polymer composite film.

[0066] The carbon dot aqueous solution prepared by the present invention has a positive zeta potential, can be dispersed in an anionic polymer solution, and is used to prepare a carbon dot polymer composite film.

[0067] The carbon dots prepared by the present invention have excellent luminescence performance, and the prepared luminescent material also has excellent luminescence performance.

[0068] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0069] Example 1

[0070] (1) 0.5 g of polyethyleneimine (PEI) having a weight average molecular weight of 1800, 0.08 g of thiamine hydrochloride (TH) and water were mixed (the mass ratio of polyethyleneimine to thiamine hydrochloride was 0.5:0.08, and the mass ratio of polyethyleneimine to water was 1:30), and after being subjected to ultrasonic vibration until completely dissolved, the pH value was adjusted to 8 with a sodium hydroxide solution to obtain a mixed solution;

[0071] (2) The mixed solution was transferred and sealed in the polytetrafluoroethylene liner of the reaction kettle, and placed in an oven at 180°C for reaction for 14 hours. After the reaction, the solution was filtered with a syringe filter with a 0.45 μm aqueous filter membrane to obtain a yellow clear carbon dot solution. After dialyzing with a 500 Da permeable membrane for 48 hours and vacuum concentrating at 80°C, the solution was freeze-dried to obtain a yellow paste-like solid, which is fluorescent carbon dots with room temperature phosphorescence properties, denoted as PEI-TH-CPDs.

[0072] Example 2

[0073] The weight average molecular weight of polyethyleneimine in step (1) of Example 1 was replaced by 600, and the other parameters were the same as those in Example 1.

[0074] Example 3

[0075] The weight average molecular weight of polyethyleneimine in step (1) of Example 1 was replaced by 10,000, and the other parameters were the same as those in Example 1.

[0076] Example 4

[0077] The weight average molecular weight of polyethyleneimine in step (1) of Example 1 was replaced by 70,000, and the other parameters were the same as those in Example 1.

[0078] The carbon dot solutions prepared in Examples 1 to 4 were scanned by fluorescence spectrum. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that the fluorescence intensity is highest when the weight average molecular weight of polyethyleneimine is 1800.

[0079] Example 5

[0080] The amount of thiamine hydrochloride in step (1) of Example 1 was replaced with 0.02 g. At this time, the mass ratio of polyethyleneimine to thiamine hydrochloride was 0.5:0.02. Other parameters were the same as those in Example 1.

[0081] Example 6

[0082] The amount of thiamine hydrochloride in step (1) of Example 1 was replaced with 0.04 g. At this time, the mass ratio of polyethyleneimine to thiamine hydrochloride was 0.5:0.04. Other parameters were the same as those in Example 1.

[0083] Example 7

[0084] The amount of thiamine hydrochloride in step (1) of Example 1 was replaced with 0.16 g. At this time, the mass ratio of polyethyleneimine to thiamine hydrochloride was 0.5:0.16. Other parameters were the same as those in Example 1.

[0085] Example 8

[0086] The amount of thiamine hydrochloride in step (1) of Example 1 was replaced with 0.32 g. At this time, the mass ratio of polyethyleneimine to thiamine hydrochloride was 0.5:0.32. Other parameters were the same as those in Example 1.

[0087] Example 9

[0088] The amount of thiamine hydrochloride in step (1) of Example 1 was replaced with 0.35 g. At this time, the mass ratio of polyethyleneimine to thiamine hydrochloride was 0.5:0.35. Other parameters were the same as those in Example 1.

[0089] Fluorescence spectroscopy was performed on the carbon dot solutions prepared in Examples 1 and 5 to 9. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the fluorescence intensity is highest when the dosage of polyethyleneimine is 0.5g, the dosage of thiamine hydrochloride is 0.08g, and the mass ratio of polyethyleneimine to thiamine hydrochloride is 0.5:0.08.

[0090] Example 10

[0091] The amount of thiamine hydrochloride in step (1) of Example 1 was replaced with 0.4 g. At this time, the mass ratio of polyethyleneimine to thiamine hydrochloride was 0.5:0.4. Other parameters were the same as those in Example 1.

[0092] Embodiment 11

[0093] The amount of thiamine hydrochloride in step (1) of Example 1 was replaced with 0.48 g. At this time, the mass ratio of polyethyleneimine to thiamine hydrochloride was 0.5:0.48. Other parameters were the same as those in Example 1.

[0094] Example 12

[0095] The amount of thiamine hydrochloride in step (1) of Example 1 was replaced with 0.5 g. At this time, the mass ratio of polyethyleneimine to thiamine hydrochloride was 0.5:0.5. Other parameters were the same as those in Example 1.

[0096] Example 13

[0097] The amount of thiamine hydrochloride in step (1) of Example 1 was replaced with 0.55 g. At this time, the mass ratio of polyethyleneimine to thiamine hydrochloride was 0.5:0.55. Other parameters were the same as those in Example 1.

[0098] Embodiment 14

[0099] The amount of thiamine hydrochloride in step (1) of Example 1 was replaced with 0.64 g. At this time, the mass ratio of polyethyleneimine to thiamine hydrochloride was 0.5:0.64. Other parameters were the same as those in Example 1.

[0100] Embodiment 15

[0101] The amount of thiamine hydrochloride in step (1) of Example 1 was replaced with 0.8 g. At this time, the mass ratio of polyethyleneimine to thiamine hydrochloride was 0.5:0.8. Other parameters were the same as those in Example 1.

[0102] Example 16

[0103] The amount of thiamine hydrochloride in step (1) of Example 1 was replaced with 1.12 g. At this time, the mass ratio of polyethyleneimine to thiamine hydrochloride was 0.5:1.12. Other parameters were the same as those in Example 1.

[0104] Embodiment 17

[0105] The amount of thiamine hydrochloride in step (1) of Example 1 was replaced with 1.6 g. At this time, the mass ratio of polyethyleneimine to thiamine hydrochloride was 0.5:1.6. Other parameters were the same as those in Example 1.

[0106] Embodiment 18

[0107] The pH value of the mixed solution in step (1) of Example 1 was replaced with 5, and the other parameters were the same as those of Example 1.

[0108] Embodiment 19

[0109] The pH value of the mixed solution in step (1) of Example 1 was replaced with 6, and the other parameters were the same as those of Example 1.

[0110] Embodiment 20

[0111] The pH value of the mixed solution in step (1) of Example 1 was replaced with 7, and the other parameters were the same as those of Example 1.

[0112] Embodiment 21

[0113] The pH value of the mixed solution in step (1) of Example 1 was replaced with 9, and the other parameters were the same as those of Example 1.

[0114] Embodiment 22

[0115] The pH value of the mixed solution in step (1) of Example 1 was replaced by 10, and the other parameters were the same as those of Example 1.

[0116] Fluorescence spectroscopy was performed on the carbon dot solutions prepared in Examples 1 and 18 to 22. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the fluorescence intensity is highest when the pH value of the mixed solution is 8.

[0117] Embodiment 23

[0118] The reaction time in step (2) of Example 1 was replaced by 2 h, and the other parameters were the same as those in Example 1.

[0119] Embodiment 24

[0120] The reaction time in step (2) of Example 1 was replaced by 4 h, and the other parameters were the same as those in Example 1.

[0121] Embodiment 25

[0122] The reaction time in step (2) of Example 1 was replaced with 6 h, and the other parameters were the same as those in Example 1.

[0123] Embodiment 26

[0124] The reaction time in step (2) of Example 1 was replaced by 7 h, and the other parameters were the same as those in Example 1.

[0125] Embodiment 27

[0126] The reaction time in step (2) of Example 1 was replaced with 8 h, and the other parameters were the same as those in Example 1.

[0127] Embodiment 28

[0128] The reaction time in step (2) of Example 1 was replaced with 10 h, and the other parameters were the same as those in Example 1.

[0129] Embodiment 29

[0130] The reaction time in step (2) of Example 1 was replaced with 12 h, and the other parameters were the same as those in Example 1.

[0131] Embodiment 30

[0132] The reaction time in step (2) of Example 1 was replaced with 16 h, and the other parameters were the same as those in Example 1.

[0133] Fluorescence spectroscopy was performed on the carbon dot solutions prepared in Examples 1 and 23 to 30. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that the fluorescence intensity is highest when the reaction time is 14h.

[0134] Embodiment 31

[0135] The reaction temperature in step (2) of Example 1 was replaced with 120° C., and the other parameters were the same as those of Example 1.

[0136] Embodiment 32

[0137] The reaction temperature in step (2) of Example 1 was replaced with 140° C., and the other parameters were the same as those of Example 1.

[0138] Embodiment 33

[0139] The reaction temperature in step (2) of Example 1 was replaced with 160° C., and the other parameters were the same as those of Example 1.

[0140] Embodiment 34

[0141] The reaction temperature in step (2) of Example 1 was replaced with 200° C., and the other parameters were the same as those of Example 1.

[0142] Fluorescence spectroscopy was performed on the carbon dot solutions prepared in Examples 1 and 31 to 34. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that the fluorescence intensity is highest when the reaction temperature is 180℃.

[0143] Comparative Example 1

[0144] The thiamine hydrochloride in step (1) of Example 1 was replaced by phthalic acid, and the other parameters were the same as those of Example 1.

[0145] Comparative Example 2

[0146] The thiamine hydrochloride in step (1) of Example 1 was replaced by thioglycolic acid, and the other parameters were the same as those of Example 1.

[0147] Comparative Example 3

[0148] The thiamine hydrochloride in step (1) of Example 1 was replaced by cystine, and the other parameters were the same as those of Example 1.

[0149] Comparative Example 4

[0150] The thiamine hydrochloride in step (1) of Example 1 was replaced by sulfuric acid, and the other parameters were the same as those of Example 1.

[0151] Comparative Example 5

[0152] The thiamine hydrochloride in step (1) of Example 1 was replaced by citric acid, and the other parameters were the same as those of Example 1.

[0153] Fluorescence spectroscopy was performed on the carbon dot solutions prepared in Example 1 and Comparative Examples 1 to 4. The results are as follows: Figure 6 As shown. Figure 6 It can be seen that the fluorescence intensity of the carbon dots prepared by using thiamine hydrochloride as raw material in Example 1 is the highest.

[0154] The carbon dot solution prepared in Example 1 was diluted 10 times with purified water, and the fluorescence emission spectrum and fluorescence excitation spectrum within the scanning range of 220 to 650 nm were measured. The results are as follows: Figure 7 shown.

[0155] The carbon dot solution prepared in Example 1 was diluted 100 times with purified water, and purified water was used as a reference. The ultraviolet absorption spectrum of 200-600 nm was scanned, and photos of the solution were taken under sunlight and 365 nm ultraviolet light. The results are as follows: Figure 8 As shown. Figures 7-8 It can be seen that the carbon dot aqueous solution has a stable blue fluorescence emission signal at 458 nm under the excitation of 335 nm wavelength.

[0156] The carbon dot solution prepared in Example 1 was dialyzed through a 500Da permeable membrane for 24 hours, and then the dialyzate was dropped onto a copper mesh with a porous carbon membrane and naturally dried. The morphology and structure of the carbon dot solution were characterized by a field emission transmission electron microscope. The transmission scanning electron microscope image is shown in FIG. Fig. 9 shown.

[0157] The carbon dot solution prepared in Example 1 was dialyzed through a 500Da permeable membrane for 24 hours, and then its transmission scanning electron microscope image was measured. The particle size distribution was analyzed using Nano Measurer software. The obtained particle size distribution diagram is shown in FIG. Fig.10 shown.

[0158] from Figures 9-10 It can be seen that the carbon dots are highly dispersed and spherical, with a relatively uniform size and an average particle size of about 4.28nm.

[0159] The carbon dot solution prepared in Example 1 was diluted 10 times with purified water, the excitation wavelength was changed to 290-380 nm, and the fluorescence spectra under different excitation wavelengths were measured. The results are as follows: Fig.11 As shown, Fig.11 The corresponding emission wavelength and intensity curve is as follows Fig.12 shown.

[0160] Take 1 mL of the carbon dot solution prepared in Example 1, dilute it 10 times with purified water, and irradiate it under a UV lamp at 365 nm. Scan the optimal excitation wavelength and the optimal emission wavelength every 5 minutes. Measure continuously for 1 hour. The results are as follows: Fig.13 shown.

[0161] 400uL of the carbon dot solution prepared in Example 1 was added to each of 12 10mL centrifuge tubes. 1.2mL of prepared BR buffer solutions with different pH values ​​(pH=1.81, 2.87, 3.78, 4.78, 5.72, 6.80, 7.96, 8.95, 9.91, 10.88, 11.82) and aqueous solutions were added to each centrifuge tube. The fluorescence spectra of the carbon dots under different pH buffer solutions and aqueous solutions are shown in Figure 2. Fig.14 As shown. Figures 11 to 14 It can be seen that the carbon dot solution prepared by the present invention exhibits stable fluorescence emission under different pH solution environments and irradiation with a 365nm light source for different time periods. It exhibits stable fluorescence emission under excitation with different light sources at wavelengths of 290 to 380nm, and the emission peak position is 458nm.

[0162] Application Example 1

[0163] 2.0 g of boric acid was dissolved in 40 mL of ultrapure water and then 2 mL of a 60 mg / mL aqueous solution of carbon dots prepared in Example 1 was added, and ultrasonic mixing was performed for 10 min. The mouth of the beaker was covered with aluminum foil, and the mixture was placed in an oven at 180° C. and heated for 5 h. The mixture was naturally cooled to room temperature to obtain an amorphous glassy carbon dot boron oxide composite material, which was recorded as PEI-thiamine hydrochloride CPDs@B2O3.

[0164] Comparative application example 1

[0165] The carbon dot aqueous solution in Application Example 1 is replaced with pure water to obtain B2O3.

[0166] Comparative Application Example 2

[0167] The aqueous solution of carbon dots prepared in Example 1 in Application Example 1 was replaced by the aqueous solution of carbon dots prepared in Comparative Example 1, and other parameters were the same as those in Application Example 1 to obtain PEI-phthalic acid CPDs@B2O3.

[0168] Comparative Application Example 3

[0169] The aqueous solution of carbon dots prepared in Example 1 in Application Example 1 was replaced by the aqueous solution of carbon dots prepared in Comparative Example 2, and other parameters were the same as those in Application Example 1 to obtain PEI-thioglycolic acid CPDs@B2O3.

[0170] Comparative Application Example 4

[0171] The aqueous solution of carbon dots prepared in Example 1 in Application Example 1 was replaced with the aqueous solution of carbon dots prepared in Comparative Example 3, and other parameters were the same as those in Application Example 1 to obtain PEI-cystine CPDs@B2O3.

[0172] Comparative Application Example 5

[0173] The aqueous solution of carbon dots prepared in Example 1 in Application Example 1 was replaced with the aqueous solution of carbon dots prepared in Comparative Example 4, and other parameters were the same as those in Application Example 1 to obtain PEI-sulfuric acid CPDs@B2O3.

[0174] Comparative Application Example 6

[0175] The aqueous solution of carbon dots prepared in Example 1 in Application Example 1 was replaced by the aqueous solution of carbon dots prepared in Comparative Example 5, and other parameters were the same as those in Application Example 1 to obtain PEI-citric acid CPDs@B2O3.

[0176] Comparative Application Example 7

[0177] The aqueous solution of carbon dots prepared in Example 1 in Application Example 1 was replaced with molybdenum disulfide quantum dots, and other parameters were the same as those in Application Example 1 to obtain molybdenum disulfide quantum dots QDs@B2O3.

[0178] The solid of Application Example 1 was ground into powder, and phosphorescence spectra were scanned at different temperatures. Afterglow videos and photos were taken under a 356nm ultraviolet lamp. The phosphorescence spectra at different temperatures were as follows: Fig.15 The corresponding phosphorescence lifetime curve is shown in Fig.16 As shown. Figures 15-16 It can be seen that the intensity of the phosphorescence spectrum decreases with increasing temperature, and the corresponding luminescence lifetime also decreases.

[0179] The solid of Application Example 1 was ground into powder and directly heated and cooled repeatedly at 20°C and 80°C. Its phosphorescence spectrum was as follows Fig.17 As shown. Fig.17 It can be seen that the composite material prepared by the carbon dots of the present invention has a temperature reversibility of 20 to 80°C.

[0180] The solid of Application Example 1 was ground into powder and irradiated under visible light, 254nm and 365nm UV light for 2s respectively. Then the light was turned off and the afterglow pictures were taken at different light-off times. The results are as follows: Fig.18 As shown. Fig.18It can be seen that the composite material prepared by the carbon dots of the present invention can continuously emit room temperature phosphorescence for nearly 7 seconds after being irradiated with a 365nm ultraviolet lamp for 2 seconds and then turned off.

[0181] The solids in Application Example 1 and Comparative Application Examples 1 to 7 were ground into powders, irradiated with a 365nm UV lamp for 2s, and then the light was turned off to take afterglow pictures at different light-off times. The results are as follows: Fig.19 As shown. Fig.19 It can be seen from the graph that the composite material prepared by the carbon dots of the present invention has a longer phosphorescence time.

[0182] Application Example 2

[0183] Weigh 1 g of PVA into a dry beaker, add 1 mL of an aqueous solution of carbon dots prepared in Example 1 with a concentration of 60 mg / mL, make the volume to 10 mL with ultrapure water, stir in a 90°C water bath for 30 min until the PVA is completely dissolved, mix evenly until the bubbles disappear, pour it onto a film-forming glass plate, and use an adjustable film-forming device to prepare a film with a thickness of 0.05 mm. Place the film-forming glass plate in an oven and dry it at 35°C for 2 h, then cool it to form a carbon dot-polymer composite film, recorded as CPDs@PVA film.

[0184] Comparative Application Example 8

[0185] The carbon dot aqueous solution in Application Example 2 was omitted to obtain a PVA film.

[0186] The films prepared in Application Example 2 and Comparative Application Example 8 were cut into strips of 100*16.4 mm, and their tensile properties were tested. Photos were taken under a 365 nm ultraviolet light. The tensile stress-strain curves were as follows: Fig. 20 The macroscopic images of the films prepared in Application Example 2 and Comparative Application Example 8 after stretching under UV light and sunlight are shown in FIG. Fig.21 As shown, Fig.21 (a) is a macroscopic image under sunlight, and (b) is a macroscopic image under ultraviolet light. Figures 20-21 It can be seen that the tensile strength of the film prepared in Application Example 2 is nearly 3 times higher than that of the PVA film.

[0187] In summary, the carbon dots prepared in the present invention have both fluorescent and phosphorescent properties, and have high luminescence intensity and long phosphorescence afterglow time.

[0188] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing fluorescent carbon dots with room temperature phosphorescence performance, comprising the following steps: (1) mixing polyethyleneimine, thiamine hydrochloride and water to obtain a mixed solution; (2) subjecting the mixed solution obtained in step (1) to a hydrothermal reaction to obtain fluorescent carbon dots having room temperature phosphorescence properties.

2. The preparation method according to claim 1, characterized in that: The weight average molecular weight of the polyethyleneimine in the step (1) is 600 to 70,000.

3. The preparation method according to claim 1, characterized in that: In the step (1), the mass ratio of polyethyleneimine to thiamine hydrochloride is 0.5:(0.02-1.6).

4. The preparation method according to claim 1, characterized in that: The pH value of the mixed solution in step (1) is 5-10.

5. The preparation method according to claim 1, characterized in that: The mass ratio of polyethyleneimine to water in the step (1) is 1:(20-40).

6. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (2) is 120 to 200° C., and the time of the hydrothermal reaction is 2 to 16 hours.

7. The preparation method according to claim 6, characterized in that: The temperature of the hydrothermal reaction is 180° C., and the time of the hydrothermal reaction is 14 h.

8. Fluorescent carbon dots with room temperature phosphorescence properties prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the fluorescent carbon dots with room temperature phosphorescence properties as claimed in claim 8 in the preparation of luminescent materials, biomedicine, optoelectronic devices and sensors.

10. The use according to claim 9, characterized in that: The luminescent material comprises a carbon dot-boron oxide composite material or a carbon dot-polymer composite film.

Citation Information

Patent Citations

  • Phosphorus-doped fluorescent carbon point with high fluorescent quantum yield as well as preparation method and application thereof

    CN106010523A

  • Non-metallic polymer carbon point with room temperature phosphorescent performance as well as preparation method and application thereof

    CN108192602A

  • Room-temperature phosphorescent carbon dot compound and preparation method thereof

    CN111607394A

  • Carbon nanodots capable of delaying fluorescence and room-temperature phosphorescence emission as well as preparation method and application of carbon nanodots

    CN114605993A

  • Preparation method and application of molecular imprinting electrochemical sensor with double-signal probe strategy

    CN115184431A